Novel natural rubber-based epoxy coating - Yong, Ming Yee; Ang, Desmond Teck Chye; Sarih, Norazilawati Muhamad (Elsevier, 2019)
The use of renewable resources in development of polymeric products is becoming more relevant in the current times, braced by the scarcity of fossil resources and threat from global warming. The manuscript describes the preparation of epoxy resin from epoxidized natural rubber (ENR) via ultraviolet (UV) treatment, followed by investigation on the film properties of the coating produced by blending the natural rubber-based epoxy resin with pentaerythritol tetrakis(3-mercaptopropionate), PETMP as the hardener. The UV treatment involved is responsible to break down the natural rubber into smaller molecular weight fractions so that it becomes more compatible with common solvents and chemicals, and at the same time improves the solubility and viscosity of the resin. The results obtained are very encouraging, with significant reduction in the molecular weight of the rubber observed after 6 hours of UV treatment, and spectroscopic characterization suggests that substantial amount of epoxide group in the ENR was effectively preserved during the treatment for subsequent reaction with PETMP. The epoxide group in the UV-degraded ENR was found to react with the –SH group of PETMP after the two were blended, applied into film, and heated at 80 °C. The properties of the coatings produced were investigated via pencil hardness test, crosshatch adhesion tape test, thermal stability test, water, and chemical resistance test. Most of the coating formulations produced film with excellent hardness, adhesion and chemical resistance. Coating B and C are among the best coating formulations, with both recorded pencil hardness grade ≥ 4H, zero film removal in the adhesion test, no film defect observed during saltwater, acid and alkaline resistance test, and reasonably good thermal stability with onset of degradation above 200 °C.